2023
DOI: 10.1515/cppm-2022-0085
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of thorium biosorption onto protonated orange peel using the response surface methodology

Abstract: In this research work, intensifying the possibility of protonated orange peel to uptake thorium (IV) ions from aqueous solutions in a batch system was investigated and optimized using the response surface methodology. The effect of three independent process variables including thorium initial concentration, pH, and biosorbent dosage was assessed based on the central composite design. The validity of the quadratic model was verified by the coefficient of determination. The optimization results showed that the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Furthermore, according to other authors' research 52 , by using orange peel as an adsorbent in a batch system, the maximum adsorption capacity was determined to be 236.97 mg/g of adsorbent, while this value was 29.58 mg/g in this study. It was found that it shows a decrease in the amount of adsorption in the case of using the immobilization technique.…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…Furthermore, according to other authors' research 52 , by using orange peel as an adsorbent in a batch system, the maximum adsorption capacity was determined to be 236.97 mg/g of adsorbent, while this value was 29.58 mg/g in this study. It was found that it shows a decrease in the amount of adsorption in the case of using the immobilization technique.…”
Section: Resultsmentioning
confidence: 50%
“…From this point on, these peels are called protonated orange peels (POP). Protonation with nitric acid has been done to remove naturally present ions from the orange peel and thus obtain a better chemically modified orange peel where all weakly acidic sites are occupied by protons (H + ) 52 , 59 , 60 . The suspension was filtered and then the POPs were washed with distilled water and dried in an oven at 45 °C for 24 h. To perform the immobilization process, first, the protonated and dried raw peels were ground and sieved with 180 μm mesh.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Keeping radioactive substances contained is a crucial safety issue for nuclear industries [1][2][3][4][5][6] . The beta-emitting strontium (Sr)-90 radionuclide has a half-life of approximately 28 years, and it is produced by nuclear fission reactions.…”
Section: Adjusted Correlation Coefficient M Adsmentioning
confidence: 99%
“…Khamseh et al [3] investigated the adsorption of thorium (IV) ions by a protonated orange peel in a batch system using response surface methodology. They found that optimal conditions resulted in a maximum thorium uptake rate of 183.95 mg/g by evaluating the effects of initial thorium concentration, pH, and biosorbent dosage.…”
Section: Introductionmentioning
confidence: 99%